Legislatures and the Budget Process - Wehner, J. author. aut Link
X, 183 p.
Keywords: What is the role of legislatures in the budget process? Do powerful assemblies give rise to pro-spending bias? This survey of legislative budgeting tackles these questions using cross-national data and case studies. It highlights the tension between legislative authority and prudent fiscal policy, exploring strategies for reconciliation.